Physiological and Biochemical Traits of Two Major Arabidopsis Accessions, Col-0 and Ws, Under Salinity - Leschevin, Maïté; Ismael, Marwa; Quero, Anthony; San Clemente, Hélène; Roulard, Romain; Bassard, Solène; Marcelo, Paulo; Pageau, Karine; Jamet, Elisabeth; Rayon, Catherine (Frontiers in Plant Science, 2021)
Salinity affects plant growth and development as shown with the glycophyte model plant, Arabidopsis thaliana (Arabidopsis) Two Arabidopsis accessions Wassilewskija (Ws) and Columbia (Col-0), are widely used to generate mutants available from various Arabidopsis seed resources. However, these two ecotypes are known to be salt-sensitive with different degrees of tolerance. In our study, 3-week-old Col-0 and Ws plants were treated with and without 150 mM NaCl for 48, 72 or 96 h and several physiological and biochemical traits were characterized on shoots to identify any specific traits in their tolerance to salinity. Before salt treatment was carried out, a different phenotype was observed between Col-0 and Ws, whose main inflorescence stem became elongated in contrast to Col-0 which only displayed rosette leaves. Our results showed that Col-0 and Ws were both affected by salt stress with limited growth associated with a reduction in nutrient uptake, a degradation of photosynthetic pigments, an increase in protein degradation, as well as showing changes in carbohydrate metabolism and cell wall composition. These traits were often more pronounced in Col-0 and occurred usually earlier than in Ws. Tandem Mass Tags (TMTs) quantitative proteomics data correlated well with the physiological and biochemical results. The Col-0 response to salt stress was specifically characterized by a greater accumulation of osmoprotectants such as anthocyanin, galactinol and raffinose, a lower reactive oxygen detoxification capacity, and a transient reduction in galacturonic acid content. That pectin degradation was associated with an over-accumulation of the wall-associated kinase 1, WAK1, which plays a role in cell wall integrity (CWI) upon salt stress exposure. Under control conditions, Ws produced more antioxidant enzymes than Col-0. Fewer specific changes occurred in Ws in response to salt stress apart from a higher number of different fascilin-like arabinogalactan proteins and a greater abundance of expansin-like proteins, which could participate in CWI. Altogether, these data indicate that Col-0 and Ws trigger similar mechanisms to cope with salt stress, and specific changes are more likely related to the developmental stage than to their respective genetic background.